In the Pé(rré) accent of Pernambucan - de Souza, Fernando Antônio Ferreira (Seven Editora, 2023)
The perspective that emerges from the mismatch between what is read and what is heard encompasses infinite directions. The complexity of these perceptual and expressive mismatches approaches the concept of accent under the symbolic effect of the idea that as a dimension of the characteristics of the expressive speech of individuals, the accent allows speculative associations, and consequently endowed with limited rationality. This article emerges from the search to identify the thoughts of the bearer of a musical accent, an individual who is a member of a specific group outside the listener’s universe and, therefore, subject to judgments based on speculation. The accent arbitrarily starts to indicate competences associated with socio-economic status, ethnicity and geopolitical origin, as well as educational levels. This article emerges from the experience of participant observation with emic musicians from musical traditions of the oral culture of Pernambuco from 2003 to 2019, when the perré element emerged as a marker of a common language which links with the local accent. DOI:https://doi.org/10.56238/alookdevelopv1-041